The Accuracy of Large Loop Excision of the Transformation Zone Specimen Dimensions in Determining Volume: A Multicentric Prospective Observational Study. Issue 2 (April 2017) - Carcopino, Xavier; Mancini, Julien; Prendiville, Walter; Gondry, Jean; Chevreau, Julien; Lamblin, Gery; Atallah, Anthony; Lavoue, Vincent; Caradec, Claire; Baldauf, Jean-Jacques; Bryand, Angélique; Henno, Sébastien; et al.
Abstract : Objective: The aim of the study was to determine which mathematical formula of specimen dimensions is the most accurate method of determining volume of the excised specimen at loop excision of the transformation zone. Materials and Methods: A multicenter prospective observational study was conducted. A total of 258 patients who had a loop excision of the transformation zone performed as treatment of cervical intraepithelial neoplasia 2–3 were included. The dimensions and the volume of the specimen were measured at the time of the procedure, before formaldehyde fixation. The volume was measured by immersing the specimen in a graduated cylinder using Archimedes fluid displacement technique. The measured volume was compared with the calculated volume using different volume formulas, that is, a cone, a cylinder, a parallelepiped, and a hemiellipsoid. The main outcome measure was the relationship between calculated volume (using the dimensions of thickness, length, and circumference) and the measured volume of the specimen. Results: The mean (SD) thickness, length, and circumference of specimens were 8.8 mm (3.8), 12.7 mm (5.9), and 45.7 mm (16.8), respectively. The mean (SD) measured volume was 2.53 (1.49) mL. Using the formula for the volume of a cone, a cylinder, a parallelepiped and a hemiellipsoid, estimated volumes were 1.03 mL (1.22), 3.10 mL (3.65), 6.20 mL (7.31), and 2.07 mL (2.44), respectively. The highest intraclass correlation coefficient between measured and calculated volume was observed when using the formula for the volume of a hemiellipsoid specimen (0.47, 95% CI = 0.36–0.56). Conclusions: The hemiellipsoid formula is the most accurate determinant of the excised volume. Other formulas do not allow for an accurate estimation of the excised volume. Abstract : Although no mathematical formula allows for a precise calculation of the volume of LLETZ specimens, the hemiellipsoid volume mathematical formula is the most accurate.